EFNA3 Is a Prognostic Biomarker Correlated With Immune Cell Infiltration and Immune Checkpoints in Gastric Cancer - Zheng, Peng; Liu, XiaoLong; Li, Haiyuan; Gao, Lei; Yu, Yang; Wang, Na; Chen, Hao (Frontiers in Genetics, 2022)
Background: Ephrin A3 (EFNA3), like most genes in the ephrin family, plays a central role in embryonic development and can be dysregulated in a variety of tumors. However, the relationship between EFNA3 and gastric cancer (GC) prognosis and tumor-infiltrating lymphocytes remains unclear. Methods: Tumor Immune Estimation Resource (TIMER) and Gene Expression Profiling Interactive Analysis 2 (GEPIA2) were used to analyze the expression of EFNA3. Kaplan-Meier plots and GEPIA2 were used to evaluate the relationship between EFNA3 expression and GC prognosis. Univariable survival and multivariate Cox analyses were used to compare various clinical characteristics with survival. LinkedOmics database was used for gene set enrichment analysis (GSEA). TIMER database and CIBERSORT algorithm were used to examine the relationship between EFNA3 expression and immune infiltration in GC and to explore cumulative survival in GC. The relationship between EFNA3 and immune checkpoints was examined using cBioPortal genomics analysis. Finally, EFNA3 expression in GC cells and tissues was assayed using quantitative real-time polymerase chain reaction. Results: EFNA3 expression differs in a variety of cancers, and EFNA3 expression was higher in GC tissue than normal gastric tissue. GC patients with high expression of EFNA3 had worse overall survival, disease-free survival, and first progression. Multivariate analysis identified EFNA3 as an independent prognostic factor for GC. GSEA identified ribosome, cell cycle, ribosome biogenesis in eukaryotes, and aminoacyl-tRNA biosynthesis pathways as differentially enriched in patients with high EFNA3 expression. B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells were significantly negatively correlated with a variety of immune markers. EFNA3 participates in changes in GC immune checkpoint markers in a collinear manner. EFNA3 expression in HGC-27, AGS, MKN45, and NCI-N87 was cell lines higher than that in GES-1, and patients with high expression of EFNA3 had a worse prognosis. Conclusion: EFNA3 can be used as a prognostic and immune infiltration and checkpoint marker in GC patients.